New biochip immunofluorescence test for the serological diagnosis of pemphigus vulgaris and foliaceus: A review of the literature - Rachel R. Xuan; Anes Yang, MD, BMed, MPH; Dedee F. Murrell, MA, BMBCh, FAAD, MD, FACD, FRCP (Edin) (Wolters Kluwer, 2018)
The immunoassays that are available for the serological diagnosis of the more common subtypes of autoimmune blistering diseases such as pemphigus vulgaris (PV) and pemphigus foliaceus (PF) include enzyme-linked immunosorbent assay (ELISA) testing to specific antigens desmoglein (Dsg)1 and Dsg3, direct immunofluorescence (DIF), indirect immunofluorescence (IIF), and immunoblotting. A review of the literature on the biochip assay was conducted. Six studies investigated the validity of a new biochip, mosaic-based, IIF test in patients with pemphigus and demonstrated its relatively high sensitivity and specificity (Dsg3: 97.62-100%, 99.6-100%; Dsg1: 90%, 100%) in comparison with ELISA (Dsg3: 81-100%, 94-100%; Dsg1: 69-100%, 61.1-100%), and/or IIF (PV: 75-100%, 91.8-100%; PF: 67-100%) using suitable substrates. So far, validation studies of the biochip have been conducted in four countries (Germany, Italy, Turkey, and Poland) but none in the southern hemisphere. Caucasian patients were recruited as normal controls for these studies; thus, the diagnostic value of the biochip remains uncertain in population groups of other ethnicities. A range of disease control patients were recruited including patients with linear immunoglobulin A dermatosis, psoriasis, discoid lupus erythematosus, lichen planus, and noninflammatory skin diseases (e.g., squamous cell carcinoma, basal cell carcinoma, and vascular leg ulcers). Prospective studies with control patients from a diverse range of ethnicities are needed to better validate the biochip.